(untitled) (Journal of Medical Sciences, 2024)
The study analysed the first-time performance of basic nursing procedures by Tobruk University students of nursing. These involve medical handwashing, clean gloving, range of motion (ROM), and positioning. The result of the study indicated a moderate level of performance in terms of the mean score at 51.33 with an overall variance of SD=19.96. The highest mean score was found in Universal precaution clean gloving (53.96), which means the students understood the importance and practicability of this procedure. The lowest mean was recorded in positioning (43.93) while ROM had the highest variance (SD=26.66), which implied that these operations turned out to be more problematic for properly evaluating patient comfort and safety levels. While some variations in the mean scores were observed between male and female students, statistically significant differences were found in ROM and positioning (p-value < 0.05). Female students scored higher in both areas probably because of care or learning style preferences. Recommendations based on the findings were that personalized teaching, in-depth instruction, simulation learning, and continuous assessment of teaching methods are essential for student comprehension and application of these procedures. The outcomes can inform targeted education interventions and allow the students to master clinical practice more effectively. For future research, an increased sample size and other mediating variables could illuminate the role of gender in influencing performance for nursing education.